PELATIHAN KEWIRAUSAHAAN DAN UMKM OLEH PT PLN UIP SUMBAGSEL DALAM MENDUKUNG UMKM NAIK KELAS DI DESA AIR SEMPIANG KABUPATEN KEPAHIANG PROVINSI BENGKULU - Alfitri, Alfitri; Kholek, Abdul; Abror, Muhammad Yusuf; Nasyaya, Annada; Simarmata, Marudut J.F.; Anugrah, Erwin C; Pahira, Lira; Zalyanti, Detia; Akbar, Dinar Tri (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the beneficiaries of the TJSL (Social and Environmental Responsibility) Program initiated by PT PLN (Persero) UIP Sumbagsel is Putri Land Bouw MSMEs which is located in Air Sempiang Village, Kepahiang Regency, Bengkulu Province. This is aimed at fulfilling its commitment to encourage and be involved in the advancement of Micro, Small and Medium Enterprises into more advanced and independent creative economic enterprises. Training is a form of initial encouragement which is quite important in providing information, education and discussion forums. Training is also very important in cultivating an entrepreneurial spirit. In this case, the TJSL program for Putri Land Bouw MSMEs was carried out to provide entrepreneurship and MSMEs training. The training was carried out using seminar methods, discussions, simulations, practice and also post tests, all of which were aimed at deepening the understanding of MSMEs Putri Land Bouw entrepreneurship. The result of the training was that the training participants were able to understand the material presented by the resource person well. This can be proven by an increase in knowledge before training and after training as seen from the results of the average pre-test and post-test scores. Participants were also quite active in questions and answers and discussions